2020
DOI: 10.1007/s40489-020-00198-8
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Scoping Review of Social, Educational, and Psychological Research on Individuals with Autism Spectrum Disorder and their Family Members in Arab Countries and Cultures

Abstract: Cultural dimensions of autism spectrum disorder (ASD) are relatively unexplored in the research literature. The current study is a systematic scoping review describing social, educational, and psychological research focused on individuals with ASD and their family members in Arab countries and cultures. Seventy studies met eligibility criteria. Most of the studies were from Jordan, Saudi Arabia, and Lebanon. Most of the identified research addressed three major domains: the prevalence of ASD and diagnosis issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…28 The reality is that pediatricians are often not trained or prepared to provide the kind of guidance and discussion that parents need after receiving a diagnosis of ASD for their child. 23,24,27,29,30 Since the pediatricians' role in guiding families about the use of CAM is pivotal, it is crucial to examine their perceptions about the use of CAM in diverse settings.…”
Section: Role Of Pediatriciansmentioning
confidence: 99%
“…28 The reality is that pediatricians are often not trained or prepared to provide the kind of guidance and discussion that parents need after receiving a diagnosis of ASD for their child. 23,24,27,29,30 Since the pediatricians' role in guiding families about the use of CAM is pivotal, it is crucial to examine their perceptions about the use of CAM in diverse settings.…”
Section: Role Of Pediatriciansmentioning
confidence: 99%
“…To date, four literature reviews have been published on ASD research in Arab countries (Hussein and Taha, 2013 ; Salhia et al, 2014 ; Alnemary et al, 2017 ; Alallawi et al, 2020 ). Alallawi et al ( 2020 ) conducted a systematic scoping review of social, educational, and psychological research relevant to persons with ASD and their families in Arab countries. Using eight databases, Alallawi et al ( 2020 ) identified 70 studies published predominantly by researchers from Saudi Arabia and Lebanon.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Another study from the United States revealed a significant increase in the magnitude of any developmental disability including ASDs from 2009 to 2011 and 2015 to 2017. 20 Prevalence studies worldwide indicate disparities, ranging from 1.4 to 29 per 10,000 children in Middle Eastern countries 24 and 4 to 17 per 1,000 children in Europe. [25][26][27][28] However, recent Global Burden of Diseases data indicated that the highest prevalence was accounted for by south Asian countries.…”
Section: Introductionmentioning
confidence: 99%